Factores familiares y sociales que determinan el internamiento por actos delictivos de los adolescentes albergados en el centro de atención residencial hogar para niños y adolescentes "san josé" inabif derivados por los juzgados de familia de la corte superior de justicia de la libertad, durante el año 2013 - Vasquez Huaynate, Judith Anshiri (2014)
This research study has been conducted at the Centre for Residential Care Home for Children and Adolescents "San José" INABIF -Trujillo, which aims to present and describe the "FAMILY AND SOCIAL FACTORS DETERMINING THE CRIMINAL ACTS OF DETENTION TEENS", referred by the Family Court of the Superior Court of Justice La Libertad, this work was conducted with a sample of 26 wards between 12 and 18. Note that it has gotten to know through their testimony of life, situations, events, and events that came at a personal level, this way, the thesis quantitative and qualitative data are provided for this purpose various methods, techniques were applied as observation, interviews, surveys, and bibliography used to find information on family and social factors that determine the placement of adolescents in the hostel, and instruments that allowed collecting significant events of the problematic reality of offenders supervised . In the first chapter the theoretical framework where criminal and other variables acts are conceptualized in the second item problem formulation arises, hypothesis, objectives and the sample which intervened on the other hand in the third chapter deals analysis and interpretation of presenting the results obtained from the data collected during the development of research through questionnaires administered to adolescents interned at the Center for Residential Care Home for Children and Adolescents "San Jose" is presented INABIF -Trujillo, also in the fourth chapter unveils response to the analysis of data and results and discussion of results. Given the results, it indicates that adolescents hospitalized for committing criminal for them acts is an easy and quick option to meet their basic needs which lack in their homes, the influence of his circle of friends, is another indicator that leads to illegal acts, the presence of frequent arguments and physical aggression, not setting standards, lack of parental affection and family communication are elements that lead adolescents to engage in illicit crimes. In conclusion, having a thorough knowledge of the situation which traverse these teens is that members of the Centre for Residential Care Home for Children and Adolescents "San José" work effectively to contribute to their overall development through values, norms and good communication, in order to insert them into their homes encouraging education based on respect.